Transformation of the Seven Seas Characters from The Little Mermaid into Carnival Costume Design - Dinda Julia Maudy Suryalina; Naufal Arafah; M. Tavip (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
This costume design project aims to present an imaginative visual interpretation of the Seven Seas characters from The Little Mermaid, while highlighting the potential of fantasy narratives as a source of inspiration in costume design development. The primary inspiration is drawn from the book The Little Mermaid: Guide to Merfolk, which details the unique characteristics of each character and the seas they originate from. Carnival costumes were chosen as the medium of expression due to their fusion of aesthetic, cultural, and imaginative elements. The main issue addressed in this study is how to interpret the Seven Seas characters into costume designs that can effectively represent both the visual identity and narrative value of each character through the adaptation of diverse elements such as color, texture, and silhouette. The creative method refers to the concept by S.P. Gustami, which comprises three stages: (1) exploration, involving literature review and character analysis; (2) design development, which includes ideation and sketch creation; and (3) realization, presented in the form of visual costume design renderings. The outcome of this design process consists of seven carnival costume designs that visually and narratively represent the Seven Seas characters. This work is expected to contribute to the development of fantasy-based costume design and serve as a reference for future conceptual fashion design projects.